2011
DOI: 10.1510/icvts.2011.274571
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, management and outcomes of patients with acute coronary syndrome and prior coronary artery bypass surgery: findings from the second Gulf Registry of Acute Coronary Events 

Abstract: ACS patients from Middle East countries with prior CABG have adverse baseline characteristics, reported higher GRACE risk score, multivessel disease, more severe LV dysfunction, cardiogenic shock, in-hospital major bleeding, but with less incidence of STEMI with less prominent surge of cardiac biomarkers. However, there was no significant difference in mortality during hospitalization, at 30 days and at one year between ACS patients with and without prior CABG. The reasons for this 'risk-mortality' paradox nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…Likewise, the predominance of men in both groups. Females were significantly more prevalent in our population with prior CABG, a similar finding was reported in previous studies conducted on same Middle-eastern population [28], [29]. This female preponderance with prior CABG was not reported in Western population.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, the predominance of men in both groups. Females were significantly more prevalent in our population with prior CABG, a similar finding was reported in previous studies conducted on same Middle-eastern population [28], [29]. This female preponderance with prior CABG was not reported in Western population.…”
Section: Discussionsupporting
confidence: 91%
“…4 Post-CABG patients presenting with acute myocardial infarction (MI) have been shown to be older, with a greater proportion of diabetes, heart failure, and previous MI. 5,6 Nonetheless it has been demonstrated that they usually have smaller infarcts and a lower incidence of Q-wave MIs. 7,8 Therefore it has been hypothesized that a prior CABG could exert a protective effect, as a result of the double coronary circulation and ischemic preconditioning.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Furthermore, Arab patients presenting with acute coronary syndrome (ACS) with prior coronary artery bypass graft (CABG) were observed to have more severe left ventricular dysfunction but with a less prominent surge of cardiac biomarkers as compared to patients from other regions. 10 In Saudi Arabia, hypertension is present in more than 80% of patients with heart failure, making it the single strongest predictor of CHF. 11 This was later confirmed from a recent study by Assiri, indicating that both hypertension and ischemic heart disease are the major causes of heart failure among elderly Saudis.…”
mentioning
confidence: 99%